Relationships among psychoneurological symptoms and levels of C-reactive protein over 2 years in women with early-stage breast cancer - Starkweather, Angela (Support Care Cancer, 2016)
PURPOSE: The aim of the present study was to explore clusters of psychoneurological symptoms and inflammation (levels of C-reactive protein) over time in a cohort of women with early-stage breast cancer. Specifically, we examined the relationships among affective symptoms (depression, anxiety, fatigue, sleep disturbances, pain, and perceived stress), domains of cognitive performance, and levels of peripheral C-reactive over a period of 2 years. METHODS: This was a prospective, longitudinal study of 77 women diagnosed with early-stage breast cancer. Data collection, including symptom questionnaires, performance-based cognitive testing, and blood draws, took place at 5 time points: prior to initiating adjuvant chemotherapy, prior to the fourth chemotherapy treatment, and at 6, 12, and 24 months after the initiation of chemotherapy. RESULTS: Exploratory factor analysis with varimax orthogonal rotation was used to examine the covariance among symptoms at each visit. Using the factor scores and weighted sums, three clusters were identified: global cognition, affective symptoms, and cognitive efficiency. Peripheral levels of C-reactive protein were inversely correlated with the cognitive efficiency factor across time. CONCLUSIONS: The findings suggest that objectively measured domains of cognitive function occur independently of other affective symptoms that are commonly reported by women with breast cancer in long-term survivorship. The cognitive efficiency symptom cluster may be amenable to interventions targeted to biological influences that reduce levels of C-reactive protein.